From jahiliyyah to Islamic worldview: in search of an Islamic economic philosophy - Mohd Shukri Hanapi (Forum Dosen Ekonomi dan Bisnis Islam (FORDEBI), 2020)
Abstract This paper attempts to seek answers, Firstly, it intends to identify Jahiliyyah practices that are allegedly accepted and practiced in Islam. Secondly, to analyze the worldview of these Jahiliyyah-origin practices within an Islamic worldview construct. The analysis was based on selected practices of the Jahiliyyah that were adopted by Rasulullah SAW. This historiography study concludes that the similarities of these practices, if any, eventhough are similar to those practiced by the Jahiliyyah, were only restricted to its names and terms, while the structure and roots were revamped by Rasulullah SAW. The divine revelations received by Rasulullah SAW are proof that Islam is absolutely free from Jahiliyyah practices. The arguments used by those who advocate the use of conventional ideas to solve problems related to Islam are therefore, incorrect.